Rapamycin mediates mTOR signaling in reactive astrocytes and reduces retinal ganglion cell loss. (November 2018) - Li, Ningfeng; Wang, Feifei; Zhang, Qinglin; Jin, Ming; Lu, Ye; Chen, Shanshan; Guo, Cuiju; Zhang, Xu
Abstract: Damage and loss of retinal ganglion cells (RGCs) can cause visual impairment. The underlying molecular mechanisms that mediate RGC death in ischemic retinal diseases are still unclear. In this study, we sought to understand the neuroprotective effect of rapamycin, the selective inhibitor of mTORC1, on RGC survival and the cellular mechanics that mediate this effect. Recent studies have reported that the epidermal growth factor (EGF) receptor shows an increase in expression in astrocytes after injury, and this receptor can promote their transformation into reactive astrocytes. Our results, along with previous works from others, show the colocalization of phosphor-EGF receptors with the astrocyte marker glial fibrillary acidic proteins in reactive astrocytes in the injured retina. In our in vitro studies, using primary astrocyte cultures of the optic nerve head of rats, showed that rapamycin significantly blocked EGF-induced mTOR signaling mainly through the PI3K/Akt pathway in primary astrocytes, but not through the MAPK/Erk pathway. Additionally, rapamycin dramatically inhibited the activation of mTOR signaling in our ratinal ischemia-reperfusion (I/R) injury model in vivo. Astrocyte activation was assessed by immunostaining retinal flat mounts or cross sections with antibody against GFAP, and we also used western blots to detect the expression of GFAP. Taken together, these results revealed that rapamycin decreases the activation of astrocytes after retinal ischemia-reperfusion injury. Furthermore, rapamycin can improve retinal RGC survival in rats during I/R, as detected by FluoroGold labeling. Our data reveals the neuroprotective effects of rapamycin in an experimental retina injury model, possibly through decreasing glial-dependent intracellular signaling mechanisms for suppressing apoptosis of RGCs. Our study also presents an approach to targeting reactive astrocytes for the treatment of optic neurodegenerations. Highlights: Optic nerve head astrocyte play an important role in glaucoma neuron damage. Activated astrocytes express mTOR proteins and affect retinal neuron survival. Rapamycin inhibits astrocyte activation and protect retinal ganglion cells. Rapamycin should be considered as a therapeutic target in patients with glaucoma.